Effects of closo-icosahedral periodoborane salts on hypergolic reactions of 70% H2O2 with energetic ionic liquids. Issue 41 (21st September 2018) - Chinnam, Ajay Kumar; Petrutik, Natan; Wang, Kangcai; Shlomovich, Avital; Shamis, Olga; Tov, Daniel Shem; Sućeska, Muhamed; Yan, Qi-Long; Dobrovetsky, Roman; Gozin, Michael
Abstract : A number of energetic ionic liquids (EILs) have been reported as promising hydrazine-replacement fuels for hypergolic rocket propulsion. Abstract : A number of energetic ionic liquids (EILs) have been reported as promising hydrazine-replacement fuels for hypergolic rocket propulsion. However, most of these EILs were ignited using corrosive and hazardous concentrated fuming nitric acid. Very significant efforts were recently made to utilize "rocket grade" highly concentrated H2 O2 (>90%) as a "green" alternative to fuming nitric acid and N2 O4 oxidizers. Although "rocket grade" H2 O2 is more challenging to use and less safe for storage than commercially available H2 O2 (70%), the latter is not considered as a viable oxidizer for hypergolic propulsion. In this work, we focused on the development of novel iodine-rich promoters, capable of initiating hypergolic ignition reactions between a typical EIL fuel – 3-ethyl-1-methyl-1 H -imidazol-3-ium cyanotrihydroborate – and H2 O2 . Among the prepared and evaluated promoters, the top performing [FcCH2 NEtMe2 + ]2 [B12 I12 2− ] compound5 showed ignition delay times of 45 ms in the reaction of the tested EIL with H2 O2 (70%) and 17 ms with H2 O2 (95%). We believe that these findings provide a platform for the development and utilization of commercially available H2 O2 as a potential "green" oxidizer for rocket propulsion.